2003
DOI: 10.1063/1.1603347
|View full text |Cite
|
Sign up to set email alerts
|

Role of excess Mg and heat treatments on microstructure and critical current of MgB2 wires

Abstract: We present a detailed analysis of the effect of heat treatments on the microstructure, magnetization, and transport properties of MgB2 wires produced by the powder-in-tube method. We have used commercial MgB2 powder with 5 at. % Mg powder added as an additional source of magnesium and stainless steel as sheath material. We measure the dc transport critical current that can be increased or decreased by more than one order of magnitude as compared with the as-drawn wire, depending on the annealing parameters. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…The former employs powder starting materials [27], whereas the latter employs a powder of synthesized superconducting material [28]. The superconducting properties of PIT-processed MgB 2 conductors are very sensitive to the quality of the starting powder [29][30][31][32][33], particle size [34][35][36], porosity of the MgB 2 core [37,38], heat treatment temperature [34,[39][40][41], and the sheath material [27,42]. In general, ex situprocessed MgB 2 tapes show lower J c than in situ-processed tapes.…”
Section: Powder-in-tube Processmentioning
confidence: 99%
“…The former employs powder starting materials [27], whereas the latter employs a powder of synthesized superconducting material [28]. The superconducting properties of PIT-processed MgB 2 conductors are very sensitive to the quality of the starting powder [29][30][31][32][33], particle size [34][35][36], porosity of the MgB 2 core [37,38], heat treatment temperature [34,[39][40][41], and the sheath material [27,42]. In general, ex situprocessed MgB 2 tapes show lower J c than in situ-processed tapes.…”
Section: Powder-in-tube Processmentioning
confidence: 99%
“…Giunchi et al also observed the presence of several grains of size 100 m after processing at 950 ºC in a similar experiment [30], suggesting that such fine grain size is due potentially to the use of a lower reaction temperature (750 ºC), which limits grain growth. Such homogeneous microstructure is attributed presence of excess Mg during reaction, which is known for improving grain connectivity, elimination of microcracks, facilitating recrystallization and avoiding B-rich impurities [35].…”
Section: Methodsmentioning
confidence: 99%
“…We packed MgB 2 powder into stainless steel tubes (inner and outer diameters 4.6 and 6.4 mm) and cold-drew them into round wires with external diameter in the range of 0.8-1.4 mm, with one intermediate annealing. This results in MgB 2 cores of very uniform, circular cross section, with diameters of 0.5-0.9 mm corresponding to f ∼ 45% and no reaction between the sheath and the superconductor [8,9].…”
mentioning
confidence: 99%
“…We have shown [8,9] that, by adding 5 at.% Mg to the initial powder, heat-treating long lengths of wire with sealed ends to avoid Mg loss, and by choosing appropriate annealing conditions, the microcracks produced by the drawing (the most severe current-limiting factor in the as-drawn wires) can be healed due to a recrystallization promoted by the excess Mg.…”
mentioning
confidence: 99%